Бізнес-модель як передумова реалізації стартап-проекту - Данкеєва, Оксана Миколаївна; Воловідник, Крістіна Тарасівна; Круглікова, Марія Юріївна (My University, 2021)
В статье определена роль бизнес-модели при реализации стартап-проекта. Рассмотрена и исследована бизнес-идея по внедрению стартап-проекта, которая заключается в создании онлайн-платформы для разработки дизайна и конструирования одежды. На этой основе представлена общая характеристика будущего бизнеса и разработана бизнес-модель стартап-проекта. Приведена схема процесса обслуживания клиентов на ІТ платформе. Предложена характеристика потребительского сегмента, на которую рассчитана деятельность стартап-проекта. Определены основные ценности предложения, которые помогут стартап-проекту определиться со стратегическим направлением. Приведены особенности этапов продвижения продукта и обратная связь с потенциальными клиентами. Приведены характеристики основных направлений деятельности ключевых партнеров на начальных этапах реализации стартап-проекта. Практическое применения бизнес-моделей заключается преобразование идеи в жизнеспособность будущего стартапа в современных условиях. In recent years, the concept of "startup," a new form of entry into the market of a new product, has become widely used in entrepreneurial activities. It is very important for the startup project team that the implementation process takes place in the short term with minimal financial costs. To realize the plan, the most responsible tasks are to determine the values of the activity, understand their capabilities when implementing the idea, determine the necessary resources, and establish the needs of the target audience. That is why an important issue when introducing and implementing a startup project on the market is the construction of a business model as a holistic understanding of future activities and a logical way to make a profit. The article defines the role of business models in the implementation of a startup project. A business idea for the implementation of a startup project consisting in the creation of an online platform for the development of design and design of clothing was considered and investigated. On this basis, a general characteristic of the future business is presented, a business model of a startup project has been developed. The diagram of the customer service process on the IT platform is given. A characteristic of the consumer segment is proposed, for which the activities of the startup project are designed. The main values of the proposal have been identified that will help the startup project decide on a strategic direction. Features of product promotion stages and feedback with potential customers are presented. The description of the main areas of activity and key partners at the initial stages of the startup project implementation is given. The purpose of the article is to develop a business model for the implementation of a startup project of an online clothing design platform. The business model allows you to transform the vision of the idea and becomes a prerequisite for building the optimal structure for implementing a startup project, which includes communicating value to the consumer segment, determining the resources necessary for implementing the idea, selecting key partners, predicting effective distribution channels, optimizing costs when creating a product and bringing it to customers.
Keywords: кафедра маркетингу; стартап-проект; цінності; бізнес-ідеї; бізнес-модель; конструювання одягу; онлайн платформа; startup project; business idea; values; business model; clothing design; online platform